Analisis Pengendapan Jumlah Volume Sedimen di dalam Saluran Primer D.I Cipicung Kecamatan Cipunagara Kabupaten Subang - Deny Ernawan (International Forum of Researchers and Lecturers, 2023)
This study aims to determine the amount of deposition due to the volume of sediment mixed with solid household waste in the canal which is high enough to become shallow, resulting in a change in the geometric cross-section of the canal in the primary canal and damage to the irrigation network of D.I. Cipicung. The method used in this research activity uses a mathematical analysis technique from Chow and Grag theory in the form of sediment depth and geometric changes in the channel cross section. The results show that the volume of sediment deposited in the primary canal is Vq primary = 16.24 m3 (section length of 50.5 meters from a channel length of 300 meters) and the geometric change in the cross section of the primary channel is A = 1.24 m2. The amount of sediment volume that affects the geometric changes in the cross-section of the primary channel that needs to be repaired is that the canal linings are still alluvial with construction linings, removal of sediment that has been mixed with solid waste, and periodic maintenance.